2023
DOI: 10.2138/am-2022-8370
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Fe5O6 and its relation to other Fe-Mg-oxides at high pressures and temperatures

Abstract: The stability of Fe 5 O 6 has been experimentally determined under pressuretemperature conditions relevant for the Earth's deeper upper mantle down to the This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, twinning on the {311} planes in magnetite can also result from the retrograde reaction of other iron oxide phases such as Fe 5 O 6 (Woodland et al 2023). On the other hand, the {100} and {113} lamellae in our recovered defect magnetite, which we interpret to have formed from a hp-O 4 phase at P and T (see above), can also help to distinguish one precursor candidate from another.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Nevertheless, twinning on the {311} planes in magnetite can also result from the retrograde reaction of other iron oxide phases such as Fe 5 O 6 (Woodland et al 2023). On the other hand, the {100} and {113} lamellae in our recovered defect magnetite, which we interpret to have formed from a hp-O 4 phase at P and T (see above), can also help to distinguish one precursor candidate from another.…”
Section: Discussionmentioning
confidence: 70%
“…Analysis of diffraction patterns (Online Materials Fig. (Lavina and Meng 2015;Woodland et al 2015Woodland et al , 2023 were identified in the powder XRD pattern. Its presence might be also attributed to a small degree of reduction during the experiment.…”
Section: Experimental Run Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small grain size of these particles (< 1 µm), we were not able to quantitatively analyze this phase. However, recent high-pressure experiments on the FeO-Fe 3 O 4 system revealed that at pressures above about 8-9 GPa two other phases, namely Fe 4 O 5 and Fe 5 O 6, exist, whereby at constant P and T, but moderately increasing ƒ O2 , wüstite (Fe 1-x O) is followed by Fe 5 O 6 and then Fe 4 O 5 and still later Fe 2 O 3 (Lavina et al 2011;Lavina and Meng 2015;Myhill et al 2016;Hikosaka et al 2019;Woodland et al 2022).…”
Section: Na-rich Shock Vein Within a Pre-existing Analcime Veinletmentioning
confidence: 99%